Combined impacts of future climate‐driven vegetation changes and socioeconomic pressures on protected areas in Africa. Issue 6 (13th October 2022) - Martens, Carola; Scheiter, Simon; Midgley, Guy F.; Hickler, Thomas
Abstract: Africa's protected areas (PAs) are the last stronghold of the continent's unique biodiversity, but they appear increasingly threatened by climate change, substantial human population growth, and land‐use change. Conservation planning is challenged by uncertainty about how strongly and where these drivers will interact over the next few decades. We investigated the combined future impacts of climate‐driven vegetation changes inside African PAs and human population densities and land use in their surroundings for 2 scenarios until the end of the 21 st century. We used the following 2 combinations of the shared socioeconomic pathways (SSPs) and representative greenhouse gas concentration pathways (RCPs): the "middle‐of‐the‐road" scenario SSP2–RCP4.5 and the resource‐intensive "fossil‐fueled development" scenario SSP5–RCP8.5. Climate change impacts on tree cover and biome type (i.e., desert, grassland, savanna, and forest) were simulated with the adaptive dynamic global vegetation model (aDGVM). Under both scenarios, most PAs were adversely affected by at least 1 of the drivers, but the co‐occurrence of drivers was largely region and scenario specific. The aDGVM projections suggest considerable climate‐driven tree cover increases in PAs in today's grasslands and savannas. For PAs in West Africa, the analyses revealed climate‐driven vegetation changes combined with hotspots of high future population and land‐use pressure. Except for many PAs in North Africa, future decreases in population and land‐use pressures were rare. At the continental scale, SSP5–RCP8.5 led to higher climate‐driven changes in tree cover and higher land‐use pressure, whereas SSP2–RCP4.5 was characterized by higher future population pressure. Both SSP–RCP scenarios implied increasing challenges for conserving Africa's biodiversity in PAs. Our findings underline the importance of developing and implementing region‐specific conservation responses. Strong mitigation of future climate change and equitable development scenarios would reduce ecosystem impacts and sustain the effectiveness of conservation in Africa. Resumen: Las áreas protegidas (AP) de África son el último bastión de la biodiversidad distintiva del continente, pero cada vez están más amenazadas por el cambio climático, crecimiento sustancial de la población humana y cambio de uso de suelo. La planificación de la conservación enfrenta el reto de la incertidumbre de cuan fuerte y donde interactuarán estos factores a lo largo de las siguientes décadas. Investigamos los impactos futuros combinados de los cambios en la vegetación impulsados por el clima dentro de AP africanas y las densidades de población humana y el uso de suelo en sus alrededores en 2 escenarios hasta el final del siglo 21. Utilizamos las siguientes 2 combinaciones de las trayectorias socioeconómicas compartidas (SSP) y las trayectorias representativas de concentración de gases de invernadero (RCP): el escenario de "mitad del camino" SSP2‐RCP4.5 y el escenario recurso intensivo "desarrollo impulsado por combustibles fósiles" SSP5‐RCP8.5. Los impactos del cambio climático sobre la cobertura de árboles y el tipo de bioma (i. e., desierto, pastizal, sabana y bosque) fueron simulados con el modelo vegetación global dinámica adaptativo (aDGVM). En ambos escenarios, la mayoría de las AP fueron afectadas adversamente por lo menos por 1 de los factores, pero la coocurrencia de los factores fue mayoritariamente específica por región y escenario. Las proyecciones de MVGDa sugieren incrementos considerables en la cobertura de árboles impulsados por el clima en las AP en pastizales y sabanas actuales. Para AP en África Occidental, los análisis revelaron cambios en la vegetación impulsados por el clima combinados con sitios clave con numerosa población y gran presión de uso de suelo en el futuro. Excepto en muchos PA de África del Norte, los decrementos en la población y presiones de uso de suelo en el futuro fueron raros. A escala continental, SSP5‐RCP8.5 condujo a mayores cambios impulsados por el clima en la cobertura arbórea y en la presión de cambio de uso de suelo, mientras que SSP5‐RCP8.5 se caracterizó por una mayor presión demográfica en el futuro. Ambos escenarios SSP‐RCP implicaron mayores retos para la conservación de la biodiversidad en AP africanas. Nuestros hallazgos subrayan la importancia de desarrollar e implementar respuestas de conservación específicas para cada región. Medidas sólidas para la mitigación del cambio climático así como escenarios de desarrollo equitativo podrían reducir los impactos en el ecosistema y sustentar la efectividad de la conservación en África. 【摘要】: 非洲的保护区是非洲大陆独特生物多样性的最后堡垒, 但它们越来越受到气候变化、人口大幅增长和土地利用变化的威胁。由于不确定在未来几十年内这些驱动因素相互作用的程度和发生位点, 保护规划也面临着挑战。本研究分析了至21世纪末的两种情景下, 非洲保护区内气候驱动的植被变化以及人口密度和土地利用未来的综合影响。我们使用了以下两种共享社会经济路径(SSPs)和温室气体代表性浓度路径(RCPs)的组合:"中间路线"情景SSP2‐RCP4.5和资源密集型的"化石燃料发展"情景SSP5‐RCP8.5。我们用适应性动态全球植被模型(aDGVM)模拟了气候变化对树木覆盖和生物群落类型(即沙漠、草原、稀树草原和森林)的影响。在这两种情景下, 大多数保护区都受到了至少一种驱动因素的负面影响, 但驱动因素是否共同出现, 在很大程度上是地区和情景特异的。aDGVM的预测表明, 目前在草原和稀树草原的保护区中, 气候驱动的树木覆盖率有大幅增加。我们的分析还表明, 西非保护区中气候驱动的植被变化与未来高人口和土地利用压力的热点相重合。除了北非的许多保护区外, 未来人口和土地利用压力很少会下降。在大陆尺度上, SSP5‐RCP8.5会导致较高的气候驱动的树木覆盖变化和较高的土地利用压力, 而SSP2‐RCP4.5则会引起较高的未来人口压力。两种SSP‐RCP情景都意味着非洲保护区内的生物多样性保护面临越来越多的挑战。我们的发现强调了制定和实施针对区域的保护对策的重要性。大力减缓未来气候变化和公平的发展情景将减少对生态系统的影响, 并维持非洲保护工作的有效性。【翻译:胡怡思;审校:聂永刚】